Isolation and characterization of siderophore producing antagonistic rhizobacteria against Rhizoctonia solani. (20th May 2013) - Solanki, Manoj Kumar; Singh, Rajesh Kumar; Srivastava, Supriya; Kumar, Sudheer; Kashyap, Prem Lal; Srivastava, Alok K.; Arora, Dilip K.
Abstract Plant protection through siderophore producing rhizobacteria (SPR) has emerged as a sustainable approach for crop health management. In present study, 220 bacteria isolated from tomato rhizosphere were screened for in vitro antagonistic activity against Rhizoctonia solani AG‐4. Nine potent antagonistic strains viz., Alcaligenes sp. (MUN1, MB21, and MPF37), Enterobacter sp. (MPM1), Pseudomonas sp. (M10A and MB65), P. aeruginosa (MPF14 and MB123) and P. fluorescens (MPF47) were identified on the basis of physiological characters and 16S rDNA sequencing. These strains were able to produce hydrolytic enzymes, hydrogen cyanide, indole acetic acid, although, only few strains were able to solubilize phosphate. Two strains (MB123 and MPF47) showed significant disease reduction in glasshouse conditions were further evaluated under field conditions using three different application methods. Application of P. fluorescens (MPF47) in nursery as soil mix + seedling root treatments prior to transplantation resulted in significant disease reduction compared to control. Total chlorophyll and available iron were significantly higher in the MPF47 treated plants in contrast to infected control. In conclusion, siderophore producing bacteria MPF47 have strong biocontrol abilities and its application as soil mix + seedling root treatments provided strong shield to plant roots against R. solani and could be used for effective bio‐management of pathogen.